(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Government ethicsconstitutes the application of ethical rules to government. Over the years, alarge number of Initiatives has been undertaken by various governments, stategovernments and central ministers to usher in an era of E Government.Governments and PSU around the world are facing to reform their publicadministration institutes and deliver more efficient and cost effectiveservices, as well as better information and knowledge to their stakeholders.The paper will explore the key benefits and challenge in advancing E Governmentthrough ICT tools to develop ethics in government.